Investigation of DNA-damage and Chromosomal Aberrations in Blood Cells under the Influence of New Silver-based Antiviral Complex - Evgenii Plotnikov; Vladimir Silnikov; Andrew Gapeyev; Vladimir Plotnikov (Tabriz University of Medical Sciences, 2016)
Purpose: The problem of infectious diseases and drug resistance is becoming increasingly important worldwide. Silver is extensively used as an anti-infective agent, but it has significant toxic side effects. In this regard, it is topical to develop new silver compounds with high biological activity and low toxicity. This work is aimed to study DNA damage and chromosomal aberrations in blood cells under the influence of new silver-based compound of general formula C6H19Ag2N4LiO6S2, with antiviral activity. Methods: The comet assay was applied for the genotoxic affects assessment on mice blood leukocytes. DNA damage was determined bases on the percentage of DNA in a comet tail (tail DNA), under the influence of silver complex in different concentrations. Genotoxic effect of the tested substance on the somatic cells was determined by chromosomal aberration test of bone marrow cells of mice. Results: In the course of the experiments, no essential changes in the level of DNA damage in the cells were found, even at highest concentrations. The administration of the substance in doses up to 2.5 g/kg in mice did not cause any increase in the frequency of chromosomal aberration in bone marrow cells. Conclusion: Taking into account known silver drug genotoxic properties, the use of a given complexed silver compound has possible great advantages for potential applications in the treatment of infectious diseases.